Medical robotics - Elson,DS; Cleary,K; Dupont,P; Merrifield,R; Riviere,C (Annals of Biomedical Engineering, 2018)
Medical robotics encompasses surgical, therapeutic and rehabilitative devices that are changing medicine and healthcare. Although the field of medical robotics predates Intuitive’s da Vinci by more than a decade, it was the clinical and commercial achievements of that system that brought medical robotics to widespread patient and public attention. It is now more than 15 years since the robot began to be used for laparoscopic prostatectomy.1 Since then, research in the field has advanced tremendously due to various technological breakthroughs. Over the last few years, there has been a surge in commercial activities in medical robotics, led both by traditional medical device and technology companies as well as new start-ups. This special issue has been commissioned to capture some of the latest research being carried out by these multidisciplinary bioengineering teams and to showcase how some of these advances can impact clinical care.